Beta-blockers and ACE inhibitors are associated with improved survival secondary to ventricular tachyarrhythmia - Schupp, Tobias; Behnes, Michael; Weiß, Christel; Lang, Siegfried; Reiser, Linda; Kern-Bollow, Armin; Taton, Gabriel; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Ansari, Uzair; El-Battrawy, Ibrahim; et al. (Cardiovascular drugs and therapy, 2018)
Objective: The study sought to assess the impact of treatment with beta-blocker (BB) or ACE inhibitor/angiotensin receptor blocker (ACEi/ARB) on secondary survival in patients presenting with ventricular tachyarrhythmia. Background: Data regarding outcome of patients presenting with ventricular tachyarrhythmia treated with BB and ACEi/ARB is limited. Methods: A large retrospective registry was used including consecutive patients presenting with ventricular tachycardia and fibrillation from 2002 to 2016 on admission. Applying propensity-score matching for harmonization, the impact of “BB” and “ACEi/ARB” was comparatively evaluated. The primary prognostic outcome was long-term all-cause death at 3 years. Results: A total of 972 matched patients were included. Both patients with BB (long-term mortality rate 18 versus 27%; log rank p = 0.041; HR = 0.661; 95% CI = 0.443-0.986; p = 0.043) and with ACEi/ARB (long-term mortality rate 13 versus 23%; log rank p = 0.004; HR = 0.544; 95% CI = 0.359-0.824; p = 0.004) revealed better secondary survival compared to patients without after presenting with ventricular tachyarrhythmia on admission. The prognostic benefit of BB was comparable to ACEi/ARB (long-term mortality rate 21 versus 26%; log rank p = 0.539). Conclusion: BB and ACEi/ARB were associated with improved secondary survival in patients surviving ventricular tachyarrhythmia on admission.
Gesehen am 28.08.2019